COOKIES TEPUNG KEDELAI DAN TEPUNG JALI SEBAGAI MAKANAN SELINGAN IBU HAMIL HIPEREMESIS GRAVIDARUM GRADE 1 - Ima Holilatul Kamilah; Mona Fitria; Agus Sulaeman; Widartika Widartika (Jurnal Gizi dan Dietetik, 2022)
Hyperemesis gravidarum or persistent nausea and vomiting is common in early pregnancy. Products in the form of cookies made from local food, namely soybean flour and jali flour can be a snack for pregnant women with hyperemesis gravidarum.The purpose of this study was to determine the effect of soy flour and jali flour formulations on organoleptic properties, carbohydrate, protein, fat, iron, and water content of cookies as a snack for pregnant women with hyperemesis gravidarum. The design of this study was experimental with a completely randomized design (CRD) with one factor, namely the formulation treatment between soybean flour and jali flour F1 (30%:70%), F2 (40%:60%), and F3 (50%:50%). The panelists in this study were 30 moderately trained panelists. The results of the organoleptic test showed the best product in the F2 formula with the formulation of soybean flour and jali flour (40%:60%) which contained 416,25 kcal of energy, 9,54 grams of protein, 7,14 grams of fat, 0,16 mg of iron, and 78,45 grams of carbohydrates and 3.10 grams of water content. The results of the statistical analysis of the Kruskall Wallis test showed that there was an effect of the formulation of soybean flour and jali flour on the parameters of taste (p = 0,005), texture (p = 0,031), and overall (p = 0,002).